Implementation of Restorative Justice Towards Criminal Acts Committed by a Child: Case Study of Abuse Committed by a Minor in Palembang City in 2017 - Sari, Defitrie Nathania; Sulistyawaty, Sri; Ardini, Aida (IJBLE Scientific Publications Community Inc., 2025)
Restorative Justice is seeking a fair resolution through peace involving both parties. The aim of this research is to find out how restorative justice is implemented for criminal acts committed by children. This research uses normative procedures. This research is described descriptively using analysis of data sources. In this research, the data collection carried out is primary data, where the data collected comes from various collections of books and journals. The results of the research show that the regulation of criminal acts committed by children is still not specifically regulated in a law and legal protection for children who commit criminal acts experiences several obstacles, so to date it has not been implemented properly and is at the urgency stage.